2021
DOI: 10.1002/cbdv.202001007
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Ginsenosides (20R)‐Rg3 on H2O2‐Induced Myocardial Cell Injury by Activating Keap‐1/Nrf2/HO‐1 Signaling Pathway

Abstract: Ginsenosides (20S)‐Rg3 and (20R)‐Rg3 are famous rare ginsenosides from red ginseng, and their configurations in C‐20 are different. This study aimed to investigate the protective mechanism of ginsenosides (20S)‐Rg3 and (20R)‐Rg3 on H2O2‐induced H9C2 cells and compare their activity. The results showed that the ginsenosides (20S)‐Rg3 and (20R)‐Rg3 could increase the cell activity and the levels of GSH‐Px, SOD and CAT, and decrease activities of LDH, MDA and ROS. Further studies showed that ginsenosides (20S)‐Rg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…It is generally believed that excessively ROS levels and the decreased antioxidant enzyme and propylene glycol (MDA) levels indicate the occurrence of oxidative stress. By contrast with the LPS-induced oxidative stress model, an oxidative stress model was created by treating IPEC-J2 cells with 10 mol/mL H 2 O 2 , as previously reported ( 44 , 45 ). In the H 2 O 2 -induced oxidative stress model, baicalin significantly increased the mRNA expression of HO-1 and NQO-1 and significantly increased nuclear protein expression of Nrf2, which revealed that baicalin could alleviate oxidative stress responses in IPEC-J2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally believed that excessively ROS levels and the decreased antioxidant enzyme and propylene glycol (MDA) levels indicate the occurrence of oxidative stress. By contrast with the LPS-induced oxidative stress model, an oxidative stress model was created by treating IPEC-J2 cells with 10 mol/mL H 2 O 2 , as previously reported ( 44 , 45 ). In the H 2 O 2 -induced oxidative stress model, baicalin significantly increased the mRNA expression of HO-1 and NQO-1 and significantly increased nuclear protein expression of Nrf2, which revealed that baicalin could alleviate oxidative stress responses in IPEC-J2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, dysregulated levels of oxidation in the liver further induce liver damage. Among other things, ROS are transmitted to mitochondria via the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase system as well as the respiratory chain [9,10]. Apart from mitochondria, overexpression of cytochrome P450 2E1 (CYP2E1) and 4-Hydroxynonenal (4-HNE) further damage hepatocytes [11].…”
Section: Introductionmentioning
confidence: 99%
“…The cells were then washed with PBS three times to remove the DCFH-DA which did not enter the cells. Cellular ROS content assessment was performed using a fluorescent microscope (Olympus, Tokyo, Japan) [67].…”
Section: Evaluation Of Oxidative Stressmentioning
confidence: 99%